2014
DOI: 10.1038/ncomms5205
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic methanogenesis from organosulphur compounds under ambient conditions

Abstract: Methane in the environment is produced by both biotic and abiotic processes. Biomethanation involves the formation of methane by microbes that live in oxygen-free environments. Abiotic methane formation proceeds under conditions at elevated temperature and/or pressure. Here we present a chemical reaction that readily forms methane from organosulphur compounds under highly oxidative conditions at ambient atmospheric pressure and temperature. When using iron(II/III), hydrogen peroxide and ascorbic acid as reagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 56 publications
8
155
1
1
Order By: Relevance
“…2d). However, this observation is in line with some previous findings (Althoff et al, 2010(Althoff et al, , 2014, who showed that the abiotic formation of CH 4 due to the degradation of methionine or ascorbic acid by light or oxidants such as iron minerals is possible. In the case of methionine, it was shown that the sulfur-bound methyl group of Met was the carbon precursor of CH 4 (Althoff et al, 2014).…”
Section: Inorganic and Organic Precursors Of Chsupporting
confidence: 80%
“…2d). However, this observation is in line with some previous findings (Althoff et al, 2010(Althoff et al, , 2014, who showed that the abiotic formation of CH 4 due to the degradation of methionine or ascorbic acid by light or oxidants such as iron minerals is possible. In the case of methionine, it was shown that the sulfur-bound methyl group of Met was the carbon precursor of CH 4 (Althoff et al, 2014).…”
Section: Inorganic and Organic Precursors Of Chsupporting
confidence: 80%
“…An interesting recently described reaction, related to published work on demethylation and well-studied sulfoxidation reactions, is methane formation from methionine under oxidative conditions. [118] As an example of these biomimetic studies with well-defined systems and their complexes, we describe a few processes of bispidine-type ligands relevant to environmental transformations, also because some of the environmentally relevant mechanistic work has been done with these ligands. Note that in soils, the relevant organic matter is humic substances, and these are believed to coordinate to Fe II and Fe III to enable chemical reactions similar to the structurally well-defined model systems described here.…”
Section: Relevant Oxidation Reactionsmentioning
confidence: 99%
“…[108][109][110][111][112][113] A wide variety of published work on the stoichiometric and catalytic oxidation of organic molecules with low-molecularweight non-heme iron model complexes is available, [57,114,115] and this includes oxygen-transfer reactions, e.g. sulfoxidation, [91,116] oxidative demethylation, [117] and methane formation [118] as well as the oxidation of alkanes and alkenes, [91] which are of specific interest in the degradation of organic matter in nature. An interesting recently described reaction, related to published work on demethylation and well-studied sulfoxidation reactions, is methane formation from methionine under oxidative conditions.…”
Section: Relevant Oxidation Reactionsmentioning
confidence: 99%
See 2 more Smart Citations